Immunological and Metabolomics Tools for Health Assessment of Farmed New Zealand Chinook Salmon (Oncorhynchus tshawytscha) - Lulijwa, Ronald (Auckland University of Technology, 2022)
New Zealand’s Chinook salmon (Oncorhynchus tshawytscha) farming started in 1976 and has developed to become the number one farmed finfish in the country. New Zealand is the leading global producer and supplier of farmed O. tshawytscha. New Zealand’s O. tshawytscha production remains free from diseases that have devastated global salmon farming (Diggles, 2016). However, the recent emergence of New Zealand rickettsia-like organism (NZ-RLO) (Brosnahan et al., 2017), continued industry growth, and climate change, necessitates the development of health assessment tools. The aim of this thesis was to develop immunological and metabolomic tools for farmed O. tshawytscha health assessment. Farmed O. tshawytscha peripheral blood was characterised for cellular composition and a micro-volume blood technique was developed for isolation of fish peripheral blood mononuclear cells (PBMCs) using Lymphoprep. Differential cell counts identified five cell types including erythrocytes, lymphocytes, thrombocytes, monocytes and unquantifiable neutrophils, important in future health assessments. Isolated PBMCs enable field on-farm sampling for longitudinal studies and allow in vitro immunological assessments. Findings provided the possibility to make fish health assessments in the field without fish euthanisation. The developed micro-volume blood technique was used to isolate O. tshawytscha PBMCs. These PBMCs were used to model the functional and targeted immune cytokine responses to Gram-negative bacterial lipopolysaccharide (LPS) from Escherichia coli in vitro. Bacterial LPS stimulated biphasic reactive oxygen species (ROS) production enhanced by interferon (ifn) inducible cytokines, and phagocytosis. LPS also upregulated pro-inflammatory interferon gamma (ifnγ), tumour necrosis factor alpha (tnf-α), and anti-inflammatory interleukin-10 (il-10) 24 h post-stimulus. This provided the first report of LPS induced immunomodulation in O. tshawytscha in vitro. The results have high application potential in modelling response mechanisms to emerging NZ-RLO pathogenesis. The response mechanisms of O. tshawytscha to polyinosinic: polycytidylic acid [poly (I:C)] were investigated 24 h post-in vivo stimulation. The most striking results were observed at the metabolomic level. Poly (I:C) upregulated metabolites involved in branched‐chain amino acid (BCAA)/glutathione and transsulphuration pathways and phospholipid metabolism, while those involved in energy metabolism were downregulated. At the molecular level, poly (I:C) enhanced antiviral ifnγ in head kidney (HK) and Mx1 protein in head kidney (HK), spleen (SP) and red blood cells (RBCs). Findings provide insights into poly (I:C) induced immune‐related biomarkers at metabolic and molecular levels important in future investigations. The effects of poly (I:C) in vivo on O. tshawytscha haematology, innate immunity, serum and liver metabolite profiles, HK, and SP cytokine transcript expression, over a 5-day period post-injection were studied. Important responses included enhanced neutrophil counts and PBMC ROS production. Metabolically, poly (I:C) upregulated liver and serum metabolites involved in BCAA at day one and returned to normal by day five, while metabolites involved in glycolysis were persistently depleted. Metabolic results suggest that poly (I:C) induced response mechanisms similar to those observed in viral-infected fish, where the host metabolome is hijacked to favour viral replication. At the molecular level, poly (I:C) promoted antiviral ifnγ and Mx1, and anti-inflammatory il-10 in fish lymphoid organs, depict O. tshawytscha immune defence against infection. Results may act as a primer for developing amelioration strategies against viral infections in aquaculture. Finally, O. tshawytscha were subjected to a three-month thermal stress challenge (17°C vs 19°C-20°C) to identify blood biomarkers of thermal tolerance and growth performance (weight loss vs weight gain). Independent of growth performance, thermal stress induced leucocyte apoptosis, minor immune responses, and disturbed plasma osmoregulation via reduced Na+/K+-ATPase activity. Irrespective of culture temperature, fish that lost weight were characterised by several biomarker alterations in cellular haematology and plasma clinical chemistries suggestive of suppressed feed intake. Findings provide insights into physiological and growth effects of thermal stress on O. tshawytscha, useful in selective breeding strategies. Overall, depending on resource availability, this thesis has demonstrated the usage of classical haematology, novel flow cytometry, molecular and metabolomic tools in farmed O. tshawytscha health assessment. The thesis thus recommends an integrated approach of classical assays with the more recent flow cytometry and metabolomics approaches to promote holistic farmed teleost health assessments. Keywords Farmed Salmon; Aquaculture; Oncorhynchus tshawytscha; Metabolomics; Immunology; Flow Cytometry; Peripheral Blood Mononuclear Cells; Haematology; Biomarkers